An assession of the applicability of shared leadership tenets in Cameroon : the case of Buea municipality - Ajua, Ausler (2016)
Leadership is considered very pivotal in institutions and no single leader can boss of executing leadership alone. In spite of the fact that shared leadership ideology can be dated as far back as 1920s, there has been multitude of supposition regarding shared leadership tenets and how it can be enacted in institutions.